Letting Go of Self: The Creation of the Nonattachment to Self Scale - Whitehead, Richard; Bates, Glen; Elphinstone, Brad; Yang, Yan; Murray, Greg (Frontiers in Psychology, 2018)
The Buddhist notion of nonattachment relates to an engagement with experience with flexibility and without fixation on achieving specified outcomes. The present study sought to define, create and validate a new measure of nonattachment as it applies to notions of the self. A new construct of ‘nonattachment to self’ (NTS) was developed, defined the absence of fixation on self-related concepts, thoughts and feelings and a capacity to flexibly interact with these concepts, thoughts and feelings without trying to control them. Two studies were conducted in the development of the new scale. With expert consultation, study 1 (n = 445) established a single factor, internally consistent 7-item scale via exploratory factor analysis. Study 2 (n = 388, n = 338) confirmed the factor structure of the new 7-item scale using confirmatory factor analyses. Study 2 also found the new scale to be internally consistent, with evidence supporting its test-retest, criterion, and construct validity. Nonattachment to self emerged as a unique way of relating to the self, distinct from general nonattachment, that aligned with higher levels of well-being and adaptive functioning.